CHANGES OF COMPETITIVENESS RANKINGS IN THE CEE COUNTRIES - THE 2022 OUTLOOK: Received: 13th October 2022; Revised: 1st November 2022; 2nd November 2022 Accepted; 11th November 2022 - Varga, János; Garai-Fodor Habil, Mónika; Csiszárik-Kocsir Habil, Agnes (PEOPLE: International Journal of Social Sciences, 2022)
The study focuses on the competitiveness of the V4 countries. The aim of this study is to analyse the relative position of the V4 countries. This follows on from several comparative studies published in previous years, in which we have already dealt with the competitiveness situation of the V4 countries (Varga & Csiszárik-Kocsir, 2020; Varga, 2018; Varga & Csiszárik-Kocsir, 2015). Building on the previous data, we seek to answer the question to what extent the competitiveness of the countries in the region has changed in relation to each other and whether there has been a substantial change in the competitiveness ranking of the V4 countries. By comparing the results, we can see which of the V4 countries performs best and whether there has been a change in competitiveness at the top of the list. The comparison also makes it possible to identify the efforts made by the V4 countries to become more competitive. The 2022 snapshot is of particular interest, as the COVID-19 crisis or the Russian-Ukrainian war have had an impact on national competitiveness developments, although the effects of the latter will only be reflected in statistics and reports at a later stage. National competitiveness changes independently of these factors, so it may be necessary to determine the exact situation on a regular basis.